ROLE OF CATALYTIC REFORMING PROCESS FOR GASOLINE PRODUCTION IN ASEAN REFINERIES - A.S. Nasution; E. Jasjfi (Scientific Contributions Oil and Gas, 2005)
The crude oils processed in refineries range from sweet crudes, such as Southeast Asian light Crudes, to sour crude, suck as Middle East. Far East, and Persian Gulf. For the period 1992-2005, the average annual demand growth rate for light products (gasoline, kerosene, diesel oil) is higher than residual fuel oil. These data clearly show that the need will continue for converting additional bottom into light products, by both thermal or catalytic conversions, The passage of the Clean Air Act Amendement of 1990 in the USA has forced American refineries to install new facilities to comply with stricter specifications for fuels such as gasoline and diesel oil such as Asia-Pacific, California Air Resources Board (CARB) and European Commission (EC), Various terms in the models address qualities of the gasoline blended such as benzene, total aromatics and olefm contents, RVP, the T90 of distillation range, sulphur content, and oxygenates content45, Motor gasoline is essentially a complex mixture of hydrocarbons distilling about 40°C and 220°C and consisting of compounds generally in the range C, to C2. Gasoline components can be produced by both the distillation of crude oil and the conversion of the crude oil fraction. Catalytic reforming process using bifunctional catalyst converts low octane number heavy naphthas into reformate with a high octane number. Bi-functional catalyst containing metal site (Pt, Pt/Ge) and acid site (A1,O,CI) are generally used. The balance is most important in a bifunctional reforming catalyst, and in fact it has to be different for different duties"l The end point of the naphtha feedstock is usually limited to about 185°C, partially because of increased coke deposition on the catalyst. The reforming cata- lyst exhibits a sensitivity to the conventional impurities of naphtha feed, such as: water (moisture), organic compounds of chlor, nitrogen and sulphur, and organometallic compounds (lead, copper, iron). Sintering of the metal phase becomes effective only beyond 500°C as measured by lowering of the dispersion of platinum atom condition, at the same time coke formation on the catalyst incrases tool71, The life of the catalyst will depend both on its stability and regenerability, expressed either in months or year, or in tonnage treated for unit weight of catalyst. This paper presents briefly composition of gasoline pool, specification of commercial gasoline in Indonesia as well as ASEAN refmeries, the catalyst improvements, catalyst deactivation and catalyst re- generation of the reforming process.